'Keen to Foul Their Own Nests': Contemporary and Historical Criticism of the Permanent Joint Board on Defence of 1940. Issue 1 (29th September 2022) - Perras, Galen Roger
Abstract : page_24 other On 17 August 1940, President Franklin Roosevelt met with Canada's Prime Minister William Lyon Mackenzie King in the town of Ogdensburg, which lies just across the Canadian border in upstate New York. There the two leaders agreed on the formation of the Permanent Joint Board on Defence (PJBD) to advise on policies for the defence and security of the North American continent. The PJBD was commended on all sides, in public at least, not only in the United States and Canada but also in Britain, where the new prime minister, Winston Churchill, speaking in the House of Commons on 20 August, compared the trend towards growing cooperation between the British Empire and the United States to the relentless flow of the Mississippi river. He also referred approvingly to the Permanent Joint Board in his post-war Fulton speech, delivered on 5 March 1946, as an important element in the 'special relationship' between the British Empire and the United States. Later commentators, including John Bartlet Brebner, have also seen the Joint Board as a significant part of the 'North Atlantic Triangle'. However, as this article shows, the PJBD has also attracted plenty of criticism – both contemporary and historical.